Insights into coronavirus immunity taught by the murine coronavirus. Issue 5 (22nd March 2021) - Grabherr, Sarah; Ludewig, Burkhard; Pikor, Natalia Barbara
Abstract: Coronaviruses (CoVs) represent enveloped, ss RNA viruses with the ability to infect a range of vertebrates causing mainly lung, CNS, enteric, and hepatic disease. While the infection with human CoV is commonly associated with mild respiratory symptoms, the emergence of SARS‐CoV, MERS‐CoV, and SARS‐CoV‐2 highlights the potential for CoVs to cause severe respiratory and systemic disease. The devastating global health burden caused by SARS‐CoV‐2 has spawned countless studies seeking clinical correlates of disease severity and host susceptibility factors, revealing a complex network of antiviral immune circuits. The mouse hepatitis virus (MHV) is, like SARS‐CoV‐2, a beta‐CoV and is endemic in wild mice. Laboratory MHV strains have been extensively studied to reveal coronavirus virulence factors and elucidate host mechanisms of antiviral immunity. These are reviewed here with the aim to identify translational insights for SARS‐CoV‐2 learned from murine CoVs. Abstract : Common properties of the infection etiology, host‐pathogen interactions, and immune responses shared between the mouse hepatitis virus (MHV‐A59) and SARS‐CoV‐2. A main distinguisher of MHV from other preclinical animal models of COVID‐19 is the fully adapted host replication machinery that recapitulates a multiorgan disease.